FlixBus: toward the development of predictive analytics - Marquez, Noe Paúl de Jesús López (2018)
Data is considered today by many the new oil of the century. As the amounts of data generated increase at fast pace, so does the challenges faced by companies. With new tools and technology firms try to keep up with the ever changing nature of data in order to gain an advantage within the competitive landscape. Nevertheless there is still a long road to completely understand all data related topics. Marketing is on of the main activities that has evolved and acquired a strong data focus. This paper examines how companies can better understand data and generate more effective strategies in order to incorporate analytics into the marketing mix. The study provides a better understanding of the main data definitions and develops a case study about FlixBus a global mobility leader, which offers a framework to assess big data capabilities, such as the main sources of data, the different analytical methods and its applications and finally the main challenges that might be encountered by companies.